Study on Flow and Heat Transfer Characteristics and Anti-Clogging Performance of Tree-Like Branching Microchannels - Linqi Shui; Zhongkai Hu; Hang Song; Zhi Zhai; Jiatao Wang (Energies, 2023)
In this paper, a tree-like branching microchannel with bifurcating interconnections is designed for gas turbine blade cooling. A theoretical analysis, experimental study, and numerical simulation of the heat transfer and hydrodynamic characteristics of the tree-like branching microchannel is performed, and the influence of the total number of branching levels m on the anti-clogging performance is also studied. The results indicate that the total heat transfer ratio and pressure drop ratio are closely related to the structur ne parameters. The comprehensive thermal performance increase with an increase in the ratio of Lb/L0 and fractal dimension D. Nu/Nus, f/fs, and η are increased as m increases from 3 to 5. Furthermore, the tree-like microchannel network exhibits robustness for cooling gas turbine blades. A greater total number of branching levels and a higher Re number are advantageous for enhancing the anti-clogging performance of the tree-like branching microchannel.